An overview of molecular markers for identification of non-human fecal pollution sources - Zlender, Tanja; Rupnik, Maja (Frontiers in Microbiology, 2023)
Identifying primary sources of fecal pollution is important for assessing public health risks and implementing effective remediation strategies. To date, one of the main molecular approaches for identifying sources of fecal pollution relies on detecting molecular markers within bacterial, viral, or mitochondrial nucleic acids, that are indicative of a particular host. With a primary focus on identifying fecal pollution originating from humans, the field of fecal source tracking often places less emphasis on livestock sources, frequently leaving the problem of wildlife fecal pollution unaddressed. In this review, we summarize 55 previously published and validated molecular assays and describe methods for the detection of molecular markers that are indicative of non-human hosts. They cover a range of 15 animal species/groups with a primary focus on domestic animals including cattle, pigs, dogs, and poultry. Among assays associated with wild animals, the majority are designed to detect bird feces, while the availability of assays for detecting feces of other wild animals is limited. Both domestic and wild animals can represent a zoonotic reservoir of human enteropathogens, emphasizing the importance of their role in public health. This review highlights the need to address the complexity of fecal contamination and to include a broader range of animal species into assay validation and marker identification.